Social Media Marketing Activities, Brand Trust, and Brand Loyalty in The Insurance Industry: Evidence from Zurich Indonesia - Alam, Rindang Nur; Jahroh, Siti; Shalihati, Fithriyyah (Business Review and Case Studies, 2026)
Background: The rapid growth of social media in Indonesia, with 143 million active users, has made it the primary marketing channel for 63% of Indonesian insurance companies. Despite high digital engagement, the mechanisms linking social media marketing activities (SMMA) to brand loyalty in the insurance sector remain empirically underexplored. Purpose: This study examines how SMMA affects brand loyalty directly and indirectly through brand trust among customers of Zurich Indonesia. Design/Methodology/Approach: A quantitative cross-sectional survey of 200 active Instagram followers of @zurichid was analysed using SEM-PLS with a two-stage approach in SmartPLS 4.0. Findings/Result: SMMA significantly affects brand loyalty (β=0.247, t=3.181, p=0.001) and brand trust (β=0.469, t=5.406, p<0.001). Brand trust partially mediates the SMMA to brand loyalty pathway (β=0.241, t=4.698, p<0.001), confirming a dual-pathway loyalty mechanism. The interaction dimension (loading=0.932) emerged as the dominant SMMA driver. Conclusion: Interactive and trust-oriented social media strategies are essential for sustainable brand loyalty in the Indonesian insurance industry. Insurance companies should prioritise two-way engagement and transparent communication to strengthen both loyalty pathways simultaneously. Originality/Value:This study contributes original empirical evidence from the Indonesian insurance sector, confirming brand trust as a structurally necessary mediator in high-risk financial service contexts where perceived risk elevates trust above satisfaction as the primary loyalty determinant. Keywords: brand loyalty, brand trust, insurance industry, SEM-PLS, social media marketing activities